Human immature testicular tissue organ culture: a step towards fertility preservation and restoration - Younis, Nagham; Caldeira-Brant, Andre L.; Chu, Tianjiao; Abdalla, Shtaywy; Orwig, Kyle E. (Frontiers in Endocrinology, 2023)
Background: Cryopreservation of immature testicular tissue (ITT) is currently the only option to preserve fertility of prepubertal patients. Autologous transplantation of ITT may not be safe or appropriate for all patients. Therefore, methods to mature ITT ex vivo are needed.To Aim to investigate the feasibility of inducing in vitro spermatogenesis from ITT cryopreserved for pediatric patients prior to initiation of gonadotoxic therapy.Materials and Methods: Cryopreserved-thawed ITT from prepubertal and peripubertal patients were cultured for 7, 16, and 32 days in medium with no hormones or supplemented with 5 IU/L FSH, 1 IU/L hCG, or 5IU/L FSH+1 IU/L hCG. Samples were evaluated histologically to assess tissue integrity, and immunofluorescence staining was performed to identify VASA (DDX4)+ germ cells, UCHL1+ spermatogonia, SYCP3+ spermatocytes, CREM+ spermatids, SOX9+ Sertoli cells. Proliferation (Ki67) and apoptosis (Caspase3) of germ cells and Sertoli cells were also analyzed. Sertoli and Leydig cell maturation was evaluated by AR and INSL3 expression as well as expression of the blood testis barrier protein, CLAUDIN11, and testosterone secretion in the culture medium.Results: Integrity of seminiferous tubules, VASA+ germ cells and SOX9+ Sertoli cells were maintained up to 32 days. The number of VASA+ germ cells was consistently higher in the peripubertal groups. UCHL1+ undifferentiated spermatogonia and SOX9+ Sertoli cell proliferation was confirmed in most samples. SYCP3+ primary spermatocytes began to appear by day 16 in both age groups. Sertoli cell maturation was demonstrated by AR expression but the expression of CLAUDIN11 was disorganized. Presence of mature and functional Leydig cells was verified by INSL3 expression and secretion of testosterone into culture medium. Gonadotropin treatments did not consistently impact the number or proliferation of germ cells or somatic cells, but FSH was necessary to increase testosterone secretion over time in prepubertal samples.Conclusion: ITT were maintained in organotypic culture for up to 32 days and spermatogonia differentiated to produce primary spermatocytes in both pre-and peripubertal age groups. However, complete spermatogenesis was not observed in either group.